2007
DOI: 10.1021/bi701832b
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Conserved HAMP Domain in an Intact, Membrane-Bound Chemoreceptor:  A Disulfide Mapping Study

Abstract: The HAMP domain is a conserved motif widely distributed in prokaryotic and lower eukaryotic organisms, where it is often found in transmembrane receptors that regulate two-component signaling pathways. The motif links receptor input and output modules and is essential to receptor structure and signal transduction. Recently, a structure was determined for a HAMP domain isolated from an unusual archeal membrane protein of unknown function [Hulko, M., et al. (2006) Cell 126, 929-940]. This study uses cysteine and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
137
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(148 citation statements)
references
References 28 publications
11
137
0
Order By: Relevance
“…Our shape-function studies promote that regulation of the histidine kinase activity by the upstream poly-HAMP module could be through an in-line mechanism than the side-on interaction as suggested earlier (9). Several recent studies indicated variations in the HAMP domain structure arising out of different helix rotation, helix translation, and helix-helix crossing angle (12,13,27). Similarly, a different mechanism of signal propagation through HAMP domains had been proposed.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our shape-function studies promote that regulation of the histidine kinase activity by the upstream poly-HAMP module could be through an in-line mechanism than the side-on interaction as suggested earlier (9). Several recent studies indicated variations in the HAMP domain structure arising out of different helix rotation, helix translation, and helix-helix crossing angle (12,13,27). Similarly, a different mechanism of signal propagation through HAMP domains had been proposed.…”
Section: Discussionsupporting
confidence: 69%
“…Structurally, HAMP domains are arranged as symmetric homodimeric parallel coiled coils with each protomer having two ␣-helices, AS1 and AS2, connected by a flexible linker segment (12,13,27,37). The four-helix bundle is held together by a hydrophobic core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) (see Fig. 1A) and has since been confirmed in HAMP domains from other proteins (13)(14)(15). The Af1503 HAMP domain adopts an unusual complementary x-da conformation that is related to the canonical coiled coil form by a 26°axial rotation of all four helices (Fig.…”
mentioning
confidence: 64%
“…The HAMP AS2 helices may undergo a scissoropening motion when transitioning from kinase off to kinase on (14,19). Attractant-sensitive disulfide bond formation between CheA and receptor suggests that the N-terminal CD1 helices rotate in the PIR on ligand binding (20).…”
mentioning
confidence: 99%